Peranan Dana Institusi Masjid dalam Pembangunan Ekonomi Ummat (Masyarakat) - Manurung, Saprinal; Siregar, Saparuddin; Marliyah, Marliyah (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2024)
Mosque institutions have experienced a decline in their role and function in carrying out mu'amalah activities, this condition is because most mosques do not have health services, pre-marital guidance, educational institutions and entrepreneurship training. Mosque administrators do not provide access to economic activities around the mosque, low levels of mosque management, average age is not productive, mosque financial management is unprofessional, fund allocation for mu'amalah activities is low, mosque construction focuses on mosque architecture, there is no planning for its use. funds, division of tasks, and financial accountability reports, financial reports are often not recorded as mosque assets. This research aims to find the role of mosque institutional funds in the economic development of the community. The research method uses a qualitative approach through literature exploration. Data analysis was carried out by reviewing references, then interpretation and conclusions. The results and discussion of the research found that the sources of funds for mosque institutions (mosque institution funds) were obtained from zakat, infaq, waqf, grants and so on. Optimizing the use of mosque institutional funds in the economic development of the ummah is carried out through consumptive and productive activities, namely the construction of mosque facilities and infrastructure, assistance to the poor and travelers, business capital assistance, and economic empowerment of the ummah.